ANC Gen1: BBTA3 - BPPT 1st Prototype of Active Noise Control for Vehicle Cabin Noise. Issue 1 (June 2021) - Atmojo, A Y; Masfuri, Z; Sabrina, M; Basuki, A; Feriadi, Y; Suwarjono,; Sugianto,
Abstract: Presently, value of passenger vehicle shifted from more than conventional transporting tools. Its comfort become important consideration beside its functionality, and no exception for its cabin noise also. Vendors and engineers have given their effort in minimizing vehicle cabin noise within many methods for many years. One of them is Active Noise Control (ANC) method by giving opposite signal called anti-noise that interfere and cancel each other with the noise itself. BBTA3 - BPPT have performed development of ANC system since last year, especially for medium passenger vehicle. Implementing Least Mean Square (LMS) algorithm and broadband feedforward strategy, least significance but a promising result have been achieved by the 1st prototype that have been tested in mid of 2020. Around 1 dB of best average decrement of cabin noise have been noted for its lab-scaled testing, and less than 0.5 dB for its road test result. Comprehensive approaches have been recommended for next step of development, including algorithm enhancement, hardware specification improvement, and spin-off research about acoustic-noise energy harvesting.